Modern Palacio-Blasingame Type Curve Method to Determine Well Production Characteristics and Reserves in Fields in Indonesia - Yusrizal, Muhammad Zakiy; Edgie Yuda Kaesti; Ratna Widyaningsih; Hari Prapcoyo; Nia Nuraeni (Testing Center for Oil and Gas LEMIGAS, 2025)
Well production characteristics and reserves are critical parameters in field development planning and production optimization. In general, well production characteristics are obtained through well testing, followed by plotting and extrapolating flow rate against time, commonly referred to as the cumulative production curve. Conventional decline curve analysis models production decline under constant bottom-hole pressure during boundary-dominated flow periods. However, this approach is inadequate for analyzing data obtained during transient flow periods and requires substantial time and cost when applied to large fields with numerous wells. The modern Palacio-Blasingame type-curve method enables the integration of daily production data with reservoir information by accounting for variations in bottom-hole pressure and changes in gas pressure–volume–temperature characteristics as reservoir pressure declines. This approach enhances the accuracy of well performance evaluation and reserve estimation, provides a more comprehensive understanding of reservoir dynamics, improves efficiency by reducing analysis time and associated costs compared with the conventional decline curve methods.